Diaphorodoris alba Portmann & Sandmeier, 1960 is a valid species: molecular and morphological comparison with D. luteocincta (M. Sars, 1870) (Gastropoda: Nudibranchia) - Furfaro, Giulia; Picton, Bernard; Martynov, Alexander; Mariottini, Paolo (Zootaxa, 2016)
The nudibranch Diaphorodoris luteocincta (M. Sars, 1870) shows two colour morphotypes defined as D. luteocincta var. alba and D. luteocincta var. reticulata, which are easy to identify and which share an overlapping distribution in the Mediterranean Sea and the North-Eastern Atlantic Ocean. Their systematics has long been discussed by several authors until recently when a molecular study proposed the two varieties as intraspecific colour variability occurring within D. luteocincta species. In order to solve their ranking status, we have carried out a morphological study on anatomical characters and molecular analyses on the mitochondrial markers (COI and 16S rDNA) and the nuclear H3 gene. Results proved the usefulness of the integrative taxonomy approach in assessing species delimitation; in fact Diaphorodoris alba stat. nov. and D. luteocincta were revealed to be two different species. D. luteocincta var. reticulata is confirmed as synonym of D. luteocincta s.str. A hypothesis on phylogenetic relationship among most of the currently recognised species of the genus Diaphorodoris Iredale & O’Donoghue, 1923 is also here presented.